Determinants of diarrhoeal morbidity: The case of children under five years of age among agricultural and agro-pastoralist community of southern Ethiopia - Beyene, Hunachew; Deressa, Wakgari; Kumie, Abera; Grace, Delia (2018)
Background: Diarrhoea is a leading cause of morbidity and mortality among the under-five children in low-income countries. Despite improvements in water and sanitation coverage, studies show that diarrhoea is still a major public health problem in Ethiopia. This study was designed to determine the magnitude and risk factors of diarrhoea in the agricultural and agro-pastoralist communities of the rural Sidama zone, Southern Ethiopia. Methods: a cross-sectional study was conducted in July 2013. Interview and questionnaire were the main data gathering instruments used in the study. Data for the study was collected from 1939 mothers/caregivers of the children. The children were under five years of age during the data collection period. Structured questions were used to collect data for the study. SPSS software V 19 was used to analyze the data based on a predefined conceptual model, including interrelated determinants. Bivariate and multivariable logistic regression was computed to assess independent factors of childhood diarrhoea. Results: Slightly over 95% of the participants were from Sidama ethnic background and about 88% of them were Participants. The number of male children in the study was slightly higher (53%) than that of the female participants. The mean and median ages of the children were 33.53 and 35 months, respectively. The prevalence of diarrhoea in the two weeks prior to the study was 25.6%. The occurrence of diarrhea was significantly associated with household heads following traditional religion (Odds Ratio (OR): 2.40; 95% Confidence Interval (CI) =1.49-3.88)), living in rented or shared houses (OR: 2.00; 95% CI=1.14 -3.51), living in agro-pastoralist (OR: 1.84; 95% CI=1.29-2.63), and Midland agriculturalists areas (OR: 1.50; 95% CI=1.04-2.14). In addition, storing drinking water for more than two days (OR: 1.74; 95% CI=1.27-2.37), the presence of diarrhoea in the family members other than the index child (OR: 1.35; 95% CI=1.05-1.74), children being in the age group of 6-12 months (OR: 2.459; 95% CI=1.676-3.608) and 13-24 months (OR: 1.619; 95% CI=1.103-2.377) were strongly associated with the under-five diarrhoeal morbidity (p.0.05). Conclusions: The study showed that diarrhoea was a major health problem of the under five among the agro-pastoralist communities. Socioeconomic, environmental, household and childcare related factors have influenced the transmission of diarrhoea in the study setting. Delivery of improved sanitation and hygiene suitable for agro-pastoralist communities may have a significant importance on the child health and survival in the study area.